Adolescents’ Knowledge about Adolescent Integrated Health Centers - Laila Sholaikhah Indriani; Vinami Yulian (Indonesian Journal of Global Health Research, 2026)
Adolescents represent a population group that requires specific health services, as they face various challenges including nutritional issues, reproductive health, and mental health. The Adolescent Integrated program by Indonesia Goverment was established as a community-based health service aimed at improving adolescents’ knowledge and awareness regarding health promotion and disease prevention. This study aimed to describe the level of knowledge of adolescents regarding the Posyandu Remaja's program in the working area of Baki Public Health Center, Sukoharjo Regency. This research employed a descriptive quantitative design. A total of 99 adolescent respondents participated, all of whom were selected using total sampling techniques. Data were collected through a validated questionnaire consisting of 20 items (Cronbach’s Alpha = 0.912). Univariate analysis was used to determine the distribution of respondents’ characteristics and knowledge levels. The findings revealed that the majority of respondents had a moderate level of knowledge (77.8%), while 20.2% demonstrated good knowledge, and only 2.0% were categorized as having low knowledge. Most respondents were female adolescents aged 15 years, predominantly with a junior high school education, and the majority regularly attended Posyandu activities. These results indicate that while basic information has been delivered, adolescents’ understanding of the Posyandu program remains at a general level. The adolescent integrated health center in the Baki Public Health Center